A micromechanics based model for rate dependent compression loaded unidirectional composites. (8th February 2023) - Singh, Vivekendra; Larsson, Ragnar; Olsson, Robin; Marklund, Erik
Abstract: Strain-rate effects in a unidirectional non-crimp fabric carbon/epoxy composite are addressed. To allow for kink-band formation including strain-rate effects and damage in such composites, the paper advances a recent model focused on compression loading at small off-axis angles. The model is based on computational homogenization with a subscale represented by matrix and fibre constituents at finite deformation. The fibre constituent is assumed to be elastic transversely isotropic and the matrix is viscoelastic–viscoplastic with damage degradation. Novel model improvements of special importance to small off-axis loading relate to the isostress formulation of the homogenized response in transverse shear. In this context, an enhanced homogenized elastic response is proposed based on Halpin–Tsai corrections to account for the nonuniform stress distribution on the microscale. The model captures the strongly rate sensitive kink-band formation due to localized matrix shearing and fibre rotation, confirming the experimentally observed increase in compressive strength for high strain rates. Graphical abstract: